Simultaneous pretreatment and saccharification of oil palm empty fruit bunch using laccase-cellulase cocktail - Masran, Ruqayyah; Kamal Bahrin, Ezyana; Ibrahim, Mohamad Faizal; Phang, Lai Yee; Abd Aziz, Suraini (Elsevier BV, 2020)
Oil palm empty fruit bunch (OPEFB) can be categorized as one of the toughest lignocellulosic biomass materials to be degraded naturally due to its complexity in structure. A new biological pretreatment approach of utilizing laccase-cellulase cocktail to simultaneously pretreat and saccharify OPEFB for reducing sugars production was presented in this study. Combination of laccase and cellulase has shown to exhibit minimum inhibition at 5% and 8%, respectively. This simultaneous pretreatment and saccharification of OPEFB using laccase-cellulase cocktail comprised of laccase (25–105 U/g) and Acremonium cellulase (10–30 FPU/g) was carried out at 50 °C for 72 h. As a result, the laccase-cellulase cocktail at a ratio of 45 U/g:25 FPU/g successfully produced 10.90 g/L of reducing sugars and 32.62% of hydrolysis yield, without the need of substrate washing step after pretreatment, in which it shortens the time from a total of 144 h–72 h and reduces the utilization of extra vessels.